2018
DOI: 10.1021/jacs.8b08517
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Cyclic Co2Sn2 Cluster Using a Co Synthon

Abstract: [Ar′SnCo]2 (1, Ar′ = C6H3-2,6{C6H3-2,6-iPr2}2), a rare metal–metal bonded cobalt–tin cluster with low-coordinate tin atoms, was prepared by the reaction of [K(thf)0.2][Co(1,5-cod)2] (cod = 1,5-cyclooctadiene) with [Ar′Sn(μ-Cl)]2. This reaction illustrates a promising synthetic strategy to access uncommon metal clusters. The structure of 1 features a rhomboidal Co2Sn2 core with strong metal–metal bonds between tin and cobalt and a weaker tin–tin interaction. Reaction of 1 with white phosphorus afforded [Ar′2Sn2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 71 publications
1
21
1
6
Order By: Relevance
“…By contrast, a previously reported, related cluster compound (Ar′SnCo)2 features strong covalent Sn-Co bonds, which even have partial multiple bond character. 12 It is noteworthy that although the Tt-Co and Tt-P distances for 1-3 increase down the group, the bond angles are approximately the same (C1-Tt-Co1 127°-129°, C1-Tt-P1 102°-103°). As a consequence of the relatively short atomic radius of germanium, the terphenyl substituent and the Co(P2C2tBu2)(COD) unit in 1 are very close to each other resulting in a restricted rotation of the terphenyl ligand around the Tt-P/Tt-C bonds as evidenced by variable temperature (VT) NMR experiments.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…By contrast, a previously reported, related cluster compound (Ar′SnCo)2 features strong covalent Sn-Co bonds, which even have partial multiple bond character. 12 It is noteworthy that although the Tt-Co and Tt-P distances for 1-3 increase down the group, the bond angles are approximately the same (C1-Tt-Co1 127°-129°, C1-Tt-P1 102°-103°). As a consequence of the relatively short atomic radius of germanium, the terphenyl substituent and the Co(P2C2tBu2)(COD) unit in 1 are very close to each other resulting in a restricted rotation of the terphenyl ligand around the Tt-P/Tt-C bonds as evidenced by variable temperature (VT) NMR experiments.…”
mentioning
confidence: 90%
“…A recent work from our group has successfully utilised the reaction of white phosphorus (P4) with heterobimetallic complexes to prepare unusual polyphosphorus compounds. 12,13 Using this strategy, we have now synthesised the heavy tetraphospholide anions SnP4 2− and PbP4 2− . These hitherto unknown -aromatic molecules are stabilised by the coordination to two cobalt atoms in the triple-decker sandwich compounds [(η 4 -tBu2C2P2)2Co2(μ,η 5 :η 5 -P4Tt)] [Tt = Sn (6), Pb (7)].…”
mentioning
confidence: 99%
“…More recently, a joint study by Power, Wolf and co‐workers demonstrated that the low‐coordinate cobalt‐tin cluster 14 serves as a potent agent for one‐step P 4 activation and functionalization (Scheme 5 a). [18] During the reaction, the P 4 tetrahedron is selectively inserted into the rhombohedral Co 2 Sn 2 cluster core of 14 , during which one of the bulky, tin‐bound terphenyl substituents undergoes a migration to phosphorus, thereby forming a new P−C bond. The product 15 bears a terphenyl‐substituted P 4 chain and represented the first example of a molecular cluster compound containing phosphorus, cobalt and tin.…”
Section: Transition‐metal‐mediated Functionalization Of White Phosphorusmentioning
confidence: 99%
“…Steric shielding around the tetrel site has also been widely exploited as a strategy to provide kinetic stabilization, being terphenyl (C6H3-2,6-Ar2) substituents among the preferred choice. 30 In fact, coordination of terphenyl-stabilized tetrylenes to transition metals has already provided compelling results, [31][32][33][34][35][36][37] revealing the tunable donor/acceptor nature of the group 14 element 38,39 and the realization of its highly dynamic binding capacity. [40][41][42][43][44][45] For instance, the interconversion with tetrylidyne (M≡E-R) and tetryl (M-ER3) forms drastically modify the bonding with the transition metal and its stereoelectronic properties, producing reactive unsaturated sites amenable for divergent reactivity.…”
mentioning
confidence: 99%